PROMOSI WISATA BATIPUAH UNTUK MENINGKATKAN PENDAPATAN DAERAH BERBASIS WEBSITE - Elma Wati (Sekolah Tinggi Teknologi Industri Padang, 2016)
Batipuh is one area in the district. Batipuh , flat land district , this area will no tourism potential that has not been managed well by the government . travel , among others , the natural attractions, culinary and customs. Php is a software application that is familiar to design a website that is used as a medium for the promotion of tourism in the district Batipuah. With this website people will be more familiar with the area Batipauh and will be able to increase local revenue Keywords: Travel batipuah , Web , PHP , MySQL